Epidemiology of peripheral artery disease of lower limbs among workers to Cotonou in 2013. - Adjagba, Philippe (My University, 2017)
Background: Peripheral Artery Disease (PAD) is a real silent killer with a strong predictive value for cardiovascular cause mortality. We aim to assess the prevalence and factors associated with PAD among workers Cotonou city (BENIN). Methods: It was a cross-sectional study from June to September 2013 conducted within three societies in Cotonou area. We have done a systematic recruitment among workers, aged 18 and over, who signed the consent document. PAD was retained when ankle brachial index was ≤ 0.90. Other data collected were information on cardiovascular risk factor and socio- demographic data. SPSS 17 software was used to perform data quantitative analysis. Results: We registered 989 workers aged 23 to 78 years with a mean age of 52.3 ± 9.4 years. PAD was diagnosed in 47 (4.7%) among whom 2 (4.2%) had intermittent claudication. In univariate analysis, a significantly higher prevalence of PAD was found among workers with age ≥ 60 years (9.5% vs. 4.2%; p=0.015), female sex (8.0% vs. 3.8%; p=0.008), history of diabetes (11.5% vs. 4.2%; p=0.003) and hyperglycemia the date of survey (10.2% vs. 2.4%; p<0.001). After logistic regression analysis, age ≥ 60 years, female and diabetes history were independently associated with PAD. Conclusions: The prevalence of peripheral artery disease (PAD) among population of Cotonou was high. Some factors associated with PAD in this study are classical risk factor for PAD. But tobacco use, hypertension and dyslipidemia were not associated with high prevalence of PAD. Further investigations are needed to assess the real risk factors of PAD among black African people.
Keywords: Peripheral artery disease; Workers; Diabetes; Africa